Characterization of secreted recombinant Toxoplasma gondii surface antigen 2 (SAG2) heterologously expressed by the yeast Pichia pastoris - Fong, M.Y.; Lau, Y.L.; Zulqarnain, M. (Kluwer (now part of Springer), 2008)
The surface antigen 2 (SAG2) gene of the protozoan parasite, Toxoplasma gondii, was cloned and extracellularly expressed in the yeast Pichia pastoris. The effectiveness of the secreted recombinant SAG2 (rSAG2-S) as a serodiagnosis reagent was assessed by western blots and ELISA. In the western blot assay, rSAG2-S reacted with all Toxoplasma-antibody positive human serum samples but not with Toxoplasma-negative samples. In the ELISA, rSAG2-S yielded sensitivity rates ranging from 80 (IgG negative, IgM positive) to 100 (IgG positive, IgM negative). In vivo experiments showed that serum from mice immunized with rSAG2-S reacted specifically with the native SAG2 of T. gondii. These mice were protected when challenged with live cells of T. gondii.